Short-term Wind Power Prediction - Marzbani, Fatemeh (2014)
A Master of Science thesis in Electrical Engineering by Fatemeh Marzbani entitled, "Short-term Wind Power Prediction," submitted in June 2014. Thesis advisor is Dr. Ahmed Osman and thesis co-advisors are Dr. Mohamed Hassan and Dr. Taha Landolsi. Available are both soft and hard copies of the thesis.